Moving towards learning with one-to-one laptop: A longitudinal case study on tools, people, and institutions - Sipitakiat,A. (2015)
The purpose of this study is to investigate how new learning possibilities could take place in environments where students are saturated with laptops. Specifically, this work draws upon in situ examples collected from three schools in Thailand over a one year period to highlight how the schools are evolving using a theoretical framework that treats change as a developmental process. © ISLS.